Characteristics of the School Food Environment Affect the Consumption of Sugar-Sweetened Beverages Among Adolescents - Rocha, Luana Lara; Pessoa, Milene Cristine; Gratão, Lúcia Helena Almeida; Carmo, Ariene Silva do; Cordeiro, Nayhanne Gomes; Cunha, Cristiane de Freitas; Oliveira, Tatiana Resende Prado Rangel de; Mendes, Larissa Loures (Frontiers in Nutrition, 2021)
Sugar-sweetened beverages are widely available and accessible in school environment, and their presence and characteristics of this environment can influence their consumption. This study examines the association of drinking fountains per 100 students, soft drink sales, soft drink advertising, and the presence of street vendors and sugar-sweetened beverages consumption among adolescents in Brazil. This cross-sectional study was carried out using data from the Study of Cardiovascular Risk in Adolescents that was conducted between March 2013 and December 2014. The sample comprised 71,475 adolescents aged 12–17 years from 1,247 public and private schools in Brazilian cities. Sugar-sweetened beverages consumption was the dependent variable. The main effect was the school food environment, which was evaluated based on drinking fountains per 100 students, soft drink sales, soft drink advertising, and the presence of street vendors. Public and private schools that sold soft drinks were associated with higher average sugar-sweetened beverages consumption among adolescents. Our study highlights the importance of creating healthy school food environments by banning sugar-sweetened beverages in schools accordingly.